Causal relationship between gut microbiota and Behçet’s disease: a Mendelian randomization study - Li, Yu-Nan; Chen, Tong; Xue, Yang; Jia, Jun-Ya; Yan, Tie-Kun; Xu, Peng-Cheng (Frontiers in Microbiology, 2024)
Background: While observational epidemiological studies have suggested an association between gut microbiota and Behçet’s disease (BD), the causal relationship between the two remains uncertain. Methods Statistical data were obtained from gut microbiome Genome-Wide Association Studies (GWAS) published by the MiBioGen consortium, and genetic variation points were screened as instrumental variables (IV). Mendelian randomization (MR) study was performed using inverse variance weighted (IVW), weighted median, MR-Egger regression, simple mode, and weighted mode methods to evaluate the causal relationship between gut microbiota (18,340 individuals) and BD (317,252individuals). IVW was the main method of analysis. The stability and reliability of the results were verified using the leave-one-out method, heterogeneity test, and horizontal genetic pleiotropy test. Finally, a reverse MR analysis was performed to explore reverse causality. Result IVW results showed that the genus Parasutterella (OR = 0.203, 95%CI 0.055-0.747, P = 0.016), LachnospiraceaeNC2004group (OR = 0.101, 95%CI 0.015-0.666, P = 0.017), Turicibacter (OR = 0.043, 95%CI 0.007-0.273, P = 0.001), Erysipelatoclostridium (OR = 0.194, 95%CI 0.040-0.926, P = 0.040) were protective factors against BD, while Intestinibacter (OR = 7.589, 95%CI 1.340-42.978, P = 0.022) might be a risk factor for BD. Conclusion Our study revealed the causal relationship between gut microbiota and BD. The microbiota that related to BD may become new biomarkers, provide new potential indicators and targets for the prevention and treatment of BD.